RBTT-12. A PHASE I STUDY OF EGFRVIII-DIRECTED CAR T CELLS COMBINED WITH PD-1 INHIBITION IN PATIENTS WITH NEWLY, DIAGNOSED, MGMT-UNMETHYLATED GLIOBLASTOMA: TRIAL IN PROGRESS. (11th November 2019) - Bagley, Stephen; Desai, Arati; Binder, Zev; Nasrallah, MacLean; Hwang, Wei-Ting; Maloney-Wilensky, Eileen; Prior, Timothy; Brem, Steven; O'Rourke, Donald
Abstract: BACKGROUND: This study builds on the results of the University of Pennsylvania sponsored phase I study of a single peripheral infusion of chimeric antigen receptor (CAR) T cells targeting epidermal growth factor receptor variant III (EGFRvIII) in recurrent glioblastoma (GBM) (NCT02209376). A dose of 5x10 8 CART-EGFRvIII cells was safe, and the cells were able to expand in the host and reach the GBM tumor in the brain. In addition, there was no cross-reactivity of CART-EGFRvIII cells with wild-type EGFR normally expressed by human tissues. Some patients required tumor resection after CAR T cell infusion. In situ evaluation of the tumor microenvironment demonstrated increased and robust expression of inhibitory molecules, such as programmed death-ligand 1 (PD-L1), compared to pre–CART-EGFRvIII tumor specimens. Therefore, we hypothesized that using a combination of CART-EGFRvIII cells and a PD-1 inhibitor would improve the outcome of the treatment. METHODS: This single-center study (NCT03726515) has a single-arm, open-label, phase 1 design and will enroll 7 patients with newly diagnosed, O6-methylguanine-methyltransferase ( MGMT )-unmethylated, EGFRvIII+ GBM. Following maximal safe tumor resection, patients receive a short course of adjuvant radiation with a total dose of 40 Gy administered in 15 fractions. Peripheral IV infusions of 2x10 8 CART-EGFRvIII cells and 200mg pembrolizumab begin 2–3 weeks after completing radiation therapy. Thereafter, subjects receive CART-EGFRvIII cells + pembrolizumab in 3-week cycles for up to 3 infusions of CART-EGFRvIII cells and 4 infusions of pembrolizumab. The primary endpoint of the study is the safety and tolerability of administering multiple infusions of CART-EGFRvIII cells in combination with pembrolizumab, as measured by the occurrence of study-related adverse events. Secondary endpoints include overall survival, progression-free survival, and objective response rate. PROGRESS: At 5 June 2019, 2 patients have been enrolled and treated on study.